Forming the modern labour market: analysis of request and proposal of the working force - Stoychik, Tetyana (Professional Pedagogics, 2018)
The concept of the labour market as the most complex element of the market economy, where a worker’s and an employer’s interests are intertwined when determining the price of labour and the conditions of its functioning, are substantiated. It is proved that the labour market has constantly been in the state limelight as the reproduction of such product as workforce is the reproduction of  labour resources and in general of the productive forces of society.The situation on the world labour market has been analyzed and the economic crises that have taken place all over the world have been identified that have led to an increase in unemployment.The analysis of the labour market in Ukraine in the transition period was conducted and the deterioration of the age structure of the population, increase of demographic and economic load on the workers were revealed; as well as the employment conditions deterioration, and the weakening of incentives for high-performing labour.Some factors causing labour force supply and demand imbalances have been identified, namely: the miss of an efficient system for predicting the future need for skilled specialists; the lack of labour resources balance in the state programs of economic and social development, regional development strategies; programs and strategies for certain public life sectors development.The author analyzes the native scientists’ vision and identifies additional factors that influence the emergence of labour market imbalances, in particular: demographic (birth rate, mortality, longevity, etc.); low wages causing the most active skilled labourforce ...
Keywords: labour market; labourforce market; demand; supply; specialist; employer